Effectiveness of Discipleship in Building Self-Concept of Ex-Convicts - Rumalutur, Selfilin (Didache: Journal of Christian Education, 2025)
Ex-convicts in Indonesia faced significant social stigmatization that hindered their reintegration into society and negatively impacted their self-concept. This study examined the effectiveness of Christian discipleship programs in developing positive self-concept among ex-convicts. The research was conducted at GKIN "Pemberita Damai" Semarang, where a structured discipleship program operated weekly from January to November 2024. A qualitative phenomenological approach was employed, utilizing unstructured interviews, in-depth interviews, and observation. Six participants were purposively selected, including one pastor, two church council members, and three ex-convicts who had participated in the discipleship program. Data were analyzed using the Miles and Huberman model. The study found that spiritual mentorship through discipleship effectively addressed the identity reconstruction needs of ex-convicts by providing both spiritual foundations and a supportive community. Participants demonstrated improved self-perception, increased social confidence, and enhanced coping mechanisms. The integration of spiritual approaches with psychological rehabilitation offered a comprehensive framework for ex-convicts' reintegration. This research contributed to the development of more effective rehabilitation models that incorporate spiritual dimensions alongside traditional psychological approaches.